Notional Accounts : Notional Defined Contribution Plans as a Pension Reform Strategy - World Bank (World Bank, Washington, DC, 2012)
Notional accounts are designed to mimic a defined contribution plan, where the pension depends on contributions and investment returns. (For this reason, they are sometimes called notional, defined-contribution schemes). Pension contributions are tracked in accounts which earn a rate of return. However, in notional accounts, the return that contributions earn is a notional one, set by the government, not the product of investment returns in the markets.